Comparison of serum cartonectin (CTRP-3) level in gestational diabetes patient and healthy pregnant women and its relationship with biochemical parameters and insulin resistance - Yakar, Burkay; Karakaya, Gamzecan; Onalan, Erhan; Gursu, Mehmet Ferit (Cukurova Univ, Fac Medicine, 2020)
Purpose: The aim of this study was to compare the serum cartonectin (CTRP-3) levels of patients with gestational diabetes mellitus with the healthy control pregnant group and to investigate the relationship of cartonectin with the biochemical parameters of pregnant women. Material and Methods: The cross-sectional study was conducted between June 2016 and January 2017. A total of 30 patients with GDM and 30 healthy pregnant women were included in the study. Glucose, lipid, insulin, cpeptide and cartonectin levels were obtained from all participants after 12 hours of fasting. Results: Participants with gestational diabetes glucose, HbA1C, insulin, C-peptide, HOMA-IR, triglyceride, VLDL, HDL levels were statistically higher than the control group. Cartonectin level of the control group was 7.68 4.29, mean cartonectin level of the GDM group was 6.95 +/- 4.02 (ng / mL) and there was no statistically significant difference between the two groups. Conclusion: Glucose, HbA1c, insulin, HOMA-IR, Cpeptide, triglyceride and VLDL levels were increased in patients with GDM. Negative correlation was found between cartonectin and glucose and insulin levels in patients with gestational diabetes.
Keywords: Cartonectin (CTRP-3); gestational diabetes; insulin; insulin resistance; pregnancy